PENGARUH LINGKUNNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI SEBAGAI VARIABEL INTERVENING STUDI PADA CV. KEMBANG JOYO SAPUTRA - Andi Wahyu Saputra; Jazuli Akhmad; Suci Utami Wikaningtyas (Jurnal Riset Manajemen Akuntansi Indonesia, 2023)
The study was titled The Effect of the Work Environment and Compensation on Employee Performance Through Motivation as Intervening Variables (Study on CV. Kembang Joyo Saputra), the research formulation is Directed at the performance of CV employees. Joyo Saputra flowers have decreased. This study was agreed to test and analyze the partial influence of the Work Environment, Communication, and Motivation on cv employee performance. Kembang Joyo Saputra and To test and analyze the partial influence of the Work Environment and Compensation on CV Employee Motivation. Joyo Saputra Flowers. The research methodology is a type of research using quantitative, using a sample method saturated with population and sample of 76 employee reponden, methods of taking data with questionnaires, and using validity tests, realibitias tests, classical assumption tests, multiple regressions, t tests, and determination tests, using path analysis that is with partial indirect influence between the Work Environment and Comceptnation on Employee Performance through Motivation with tools Sobel Test Calculator analysis.The results of the study, namely the Work Environment has a positive and significant influence on employee performance on the CV. Kembang Joyo Saputra, amounting to t count (2,542) and significant 0.012, Compensation affects and significantly affects Employee Performance on CV. Joyo Saputra flowers amounted to t count (2,691) and significant (0.008). Motivation has a positive and significant effect on employee performance on the CV. Joyo Saputra flowers with a calculated value of (2,269) and a signfikan of 0.025. The Work Environment has a positive and significant influence on Employee Motivation on the CV. Joyo Saputra flowers with a calculated value of 6,365 and a significant amount of 0.000. Compensation has a positive and significant influence on employee motivation on the CV. Joyo Saputra flowers with a calculated value of 2.742 and a significant amount of 0.0046. Motivation is able to mediate the relationship of the Work Environment to Employee Performance by 2,130 and significantly by 0.016. Motivation was able to mediate the compensation relationship to Employee Performance of 2,221 and significantly by 0.013.Conclusion that there is a partial positive and significant influence between work environment, motivation, and motivation on employee performance, there is a partial positive and significant influence between the Work Environment and Compensation on employee work motivation, and there is an indirect influence between the Work Environment on Employee Performance through Motivation and there is an indirect influence between Compensation on Employee Performance through Motivation. In improving the work environment, there needs to be an improvement of new, modern, and sophisticated tools, a comfortable and safe workspace, the addition of compensation both directly and indirectly to increase employee motivation.